A highly sensitive hybridized soft piezophotocatalyst driven by gentle mechanical disturbances in water. (November 2018) - Tong, Wangshu; Zhang, Yihe; Huang, Hongwei; Xiao, Ke; Yu, Shixin; Zhou, Yan; Liu, Leipeng; Li, Haitao; Liu, Lei; Huang, Tao; Li, Min; Zhang, Qian; et al.
Abstract: Promoting semiconductor photocatalytic power is expected to address global energetic and environmental challenges. Piezophotocatalysis is an effective strategy to achieve superior catalytic performance, however, realistic applications of previous piezophotocatalysts have been hampered by the ultrasonication conditions that they require. We propose a new material design to achieve superior piezophotocatalysis by combining semiconductors with a self-powered energy cushion that is driven by gentle mechanical disturbances such as water flows. The energy cushion consists of a porous composite graphene-piezoelectric polymeric film which combines piezoelectric and dielectric power generation and stores the electricity in situ. This energy cushion results in a large and prolonged electric field in response to gentle mechanical disturbances. The electric field, in turn, enhances photocatalytic performances of TiO2, BiOI, or CdS by 300%, 21%, and 400%, respectively. In addition, this new material does not consume additional energy when promoting the catalytic performance of semiconductors. We expect the concept of combining these semiconductors with such an energy cushion to lead photocatalysis a step closer to realistic future applications. Graphical abstract: Remarkably enhanced catalytic efficiency of semiconductor particles are realized by mounting them onto a energetic cushion, which is a self-powered piezoelectric-dielectric rGO-F/PVDF-HFP composite polymeric porous film. The film effectively converts the mechanical disturbances of water flow into electric field which in turn enhanced semiconductor catalytic capabilities. fx1 Highlights: The films achieved both generation and energy storage properties. The porous structure enabled the film's high responsivity to mechanical disturbance. The porous film promoted photocatalytic capabilities of the semiconductors.